The effect of the core exercises on body composition, selected strength and performance skills in child soccer players - Genç, H.; Cigerci, A. E. (International Journal of Applied Exercise Physiology, 2020)
The purpose of the study is to examine the effect of the core exercises on body composition and selected strength and motor skills in child soccer players. The universe of the research consists of 20 soccer players. Two groups were formed, core training group (CTG, n=10, age; 12,90±0,73 year, height; 155,83±9,64 cm, body weight; 48,34±10,52 kg) and control group (CG, n=10, age; 12,80±0,63 year; height; 157,05±5,84 cm, body weight; 47,46±9,53 kg) from volunteers between 11-13 years old. 10 soccer players in CTG performed core exercise and soccer training, and 10 soccer players in CG performed only soccer training. The study lasted a total of 8 weeks, with 3 workouts per week. Age, height, body weight (BW), body mass index (BMI), body fat percentage (BFP), 10 and 30 m speed, flexibility (FL), back strength (BS), leg strength (LS), right hand grip strength (RHGS), left hand grip strength (LHGS), standing long jump (SLJ), leg lift (LL), plank (PL), back isometric (BI), push-ups (PU), shuttle (ST) tests were applied to the volunteers. Paired Samples T-Test and Independent Sample Test were used for analysis of groups in SPSS 22. Level of error was accepted as p<0,05. According to the results, a statistically significant difference was found in the height, BW, BMI, and BFP in CTG, also a significant difference was seen in CG in pre and post-test of physical measurement parameters as height, BW (p<0,05). When the post-test results of the athletes in the CTG and CG were examined, a statistically significant difference was found in favor of the CTG in LS, LL, BI and ST test in the performance parameters (p<0,05). After in-group analysis, while there was a statistically significant difference in all parameters except for 10 m and 30 m sprint in CTG; a statistically significant difference was found in FL, BS, LL, SLJ results of CG (p<0,05). In conclusion, it can be said that core exercises performed for 8 weeks have an impact on the increasing their ability to perform selected strength and motor skills of child soccer players.